Practice environment and its association with professional competence and work‐related factors: perception of newly graduated nurses. (11th February 2015) - Numminen, Olivia; Ruoppa, Eija; Leino‐Kilpi, Helena; Isoaho, Hannu; Hupli, Maija; Meretoja, Riitta
Abstract : Aim: To explore newly graduated nurses' (NGN) perception of their practice environment and its association with their self‐assessed competence, turnover intentions and job satisfaction as work‐related factors. Background: The impact of practice environment on nurses' work is important. Positive practice environments are associated with positive organisational, nurse and patient outcomes. How this applies to NGNs needs further exploration. Method: A cross‐sectional descriptive correlation design was used. Data were collected with PES‐NWI and NCS instruments from 318 Finnish registered nurses, and analysed statistically. Results: Newly graduated nurses' perception of their practice environment was mainly positive. Most positive perceptions related to collegial nurse–physician relations, and the least positive to staffing and resource adequacy. Positive perceptions were also associated with higher professional competence, higher perceptions of quality of care and lower intentions to leave the job or profession. Conclusion: The findings revealed strong and significant associations between practice environment and work‐related factors. Practice environment is an important element in supporting NGNs' competence, retention and job satisfaction. Nursing management should pay attention to NGNs' perceptions of their practice environment. Implications for nursing management: Management's ability to create and maintain positive practice environments can foster NGNs' professional development and job satisfaction, and consequently retain them in the workforce.